DEVELOPING TEACHER’S PROFESSIONAL ACTIVITIES USING INFORMATION TECHNOLOGIES - Choriyev Nurislam Nuritinovich (Web of Journals Publishing, 2024)
This article is devoted to a detailed disclosure of the pedagogical conditions, didactic possibilities, and methods for developing methodological foundations for the use of innovative approaches in the development of teachers' professional activities based on information technologies.
Keywords: Information and communication technology tools, promising areas of using ICT tools in the educational process, information and technical foundations of vocational education, teaching and learning using media.